Silently structured silent argument - Sakamoto, Yuta (Linguistik aktuell ;, 2020)
"Theoretical linguistics in the generative tradition has payed much attention to issues related to silence - children know the syntax of silence despite the fact that they do not have direct access to it throughout their language acquisition process. One of the issues that have been hotly discussed regarding silence in natural languages is whether it involves syntactic structure or not. This book is concerned with a particular instance of silence in natural languages, what is called radical pro-drop, showing that it is silently structured on the basis of novel data from Japanese as well as Chinese, Korean, Mongolian, and Turkish. The discussion in this book also has consequences for the dichotomy between PF-deletion vs. LF-copying, shedding a new light on the proper analysis of several syntactic phenomena in Japanese, including wh-in-situ and control"--